Antiparasitic lethality of sulfonamidebenzamides in kinetoplastids. Issue 4 (15th February 2017) - Hackler, Amber; Patrick, Stephen L.; Kahney, Elizabeth W.; Flaherty, Daniel P.; Sharlow, Elizabeth R.; Morris, James C.; Golden, Jennifer E.
Graphical abstract: Abstract: A sulfonamidebenzamide series was assessed for anti-kinetoplastid parasite activity based on structural similarity to the antiparasitic drug, nifurtimox. Through structure-activity optimization, derivatives with limited mammalian cell toxicity and increased potency toward African trypanosomes and Leishmania promastigotes were developed. Compound22 had the best potency against the trypanosome (EC50  = 0.010 μM) while several compounds showed ∼10-fold less potency against Leishmania promastigotes without impacting mammalian cells (EC50  > 25 μM). While the chemotype originated from an unrelated optimization program aimed at selectively activating an apoptotic pathway in mammalian cancer cells, our preliminary results suggest that a distinct mechanism of action from that observed in mammalian cells is responsible for the promising activity observed in parasites.